2016
DOI: 10.3109/17483107.2016.1139635
|View full text |Cite
|
Sign up to set email alerts
|

The effect of new dynamic splint in pinch strength in De Quervain syndrome: a comparative study

Abstract: Objective For patients with De Quervain syndrome using thumb spica orthosis is restricting, so many patient are dissatisfied with using static model. The aim of this study is to compare the effect of modified dynamic and conventional static orthoses on pinch power and functional abilities of hand in De Quervain syndrome. Method In this quasi-experimental study, palmar and lateral pinch strength of the thumb, pain and functional abilities of hand, patient's satisfaction of orthoses, were evaluated after using m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 18 publications
0
9
0
1
Order By: Relevance
“…[ 24 ] Splinting is important in protecting the joint and, minimizing or eliminating stress in the joint during daily life activities. [ 25 ] In a few studies in the literature on the use of isolated forearm-based thumb splints, the results were not successful. Weiss et al with 93 patients, success rate of 66% in the isolated steroid injection group, 57% in the steroid + forearm-based thumb splint group, and 18% in the isolated forearm-based thumb splint group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 24 ] Splinting is important in protecting the joint and, minimizing or eliminating stress in the joint during daily life activities. [ 25 ] In a few studies in the literature on the use of isolated forearm-based thumb splints, the results were not successful. Weiss et al with 93 patients, success rate of 66% in the isolated steroid injection group, 57% in the steroid + forearm-based thumb splint group, and 18% in the isolated forearm-based thumb splint group.…”
Section: Discussionmentioning
confidence: 99%
“…DQT causes pain and loss of function in the carpometacarpal joint [24] . Splinting is important in protecting the joint and, minimizing or eliminating stress in the joint during daily life activities [25] . In a few studies in the literature on the use of isolated forearm-based thumb splints, the results were not successful.…”
Section: Discussionmentioning
confidence: 99%
“…These findings led them to conclude that strict immobilization is not diseasemodifying. Nemati et al investigated the use of a traditional thumb spica cast versus a dynamic splint that allowed some wrist range of motion and found similar improvements in visual analog scale (VAS) pain and Disabilities of the Arm, Shoulder and Hand (DASH) scores, suggesting that strict immobili-zation is unnecessary 24 . In a retrospective cohort study, Lane et al demonstrated that splinting was effective in 15 of 17 patients who presented with mild symptoms but was less effective than CSI in patients with moderateto-severe symptoms 25 .…”
Section: The Role Of Immobilizationmentioning
confidence: 99%
“…Sendo o comprometimento na realização de atividades de vida diária fator relevante para alguns, devese considerar o desempenho nas atividades de vida diária ao escolher o modelo de órtese a fim de que não haja restrição da funcionalidade (O' BRIEN L, 2010;COSTA CR, et al, 2015;NEMATI Z, et al, 2016). Santos RF, et al (2017) relata que apesar das tecnologias assistivas proporcionarem funcionalidade há uma interface com o estigma.…”
Section: "Sofri a Lesão Do Nervo Radial Perdendo O Movimento De Punho E Extensão De Dedos () Ela Faz A Melhora Na Extensão Dos Dedos E Naunclassified